Triartiger caiyujiei sp. nov., a remarkable clavigerite beetle (Coleoptera, Staphylinidae, Pselaphinae) associated with Pseudolasius ants (Hymenoptera, Formicidae) from East China - Zi-Wei Yin; Xiao-Ling Niu (Deutsche Entomologische Zeitschrift)
The genus Triartiger Kubota (Pselaphinae, Clavigeritae) represents an enigmatic group of obligately myrmecophilous ant-loving beetles endemic to East Asia. Prior to this study, six species had been known across China’s mainland (Jiangxi, Fujian), Taiwan Island, and Tsushima Island of Japan, with merely two species having its symbiotic host recorded through direct collection. Herein, a remarkable new species is described: Triartiger caiyujiei sp. nov. discovered in a colony of Pseudolasius Emery (Hymenoptera, Formicidae) ants at the Tianmushan National Nature Reserve in Zhejiang Province, east China. The new taxon can be distinguished from congeners by its exceptionally elongated antennae and the most intricate elytral and abdominal trichome structures observed within the genus. The key to world species of Triartiger is updated and the current knowledge of the genus is summarised to facilitate future research.